Efektivitas Pemungutan Pajak Sebagai Variabel Moderasi Dalam Pengaruh Kesadaran Wajib Pajak UMKM Terhadap Kepatuhan Wajib Pajak di 13 Ulu Kota Palembang - Sari, Ranti Puspita; Pebriani, Reny Aziatul; Meiriasari, Vhika (Sekretariat Pusat Lembaga Komunitas Informasi Teknologi Aceh, 2025)
This study aims to analyze the influence of tax collection effectiveness, taxpayer awareness, and their interaction on taxpayer compliance. The research adopts a quantitative approach using moderated regression analysis. Data were collected through questionnaires distributed to 82 respondents, comprising MSME taxpayers in 13 Ulu Palembang City. The independent variables in this study are tax collection effectiveness and taxpayer awareness, while the dependent variable is taxpayer compliance. The findings reveal that taxpayer awareness has a significant positive effect on taxpayer compliance, indicating that higher taxpayer awareness enhances compliance with tax obligations. Conversely, tax collection effectiveness does not show a significant impact on taxpayer compliance. Moreover, the interaction between tax collection effectiveness and taxpayer awareness does not significantly moderate their effect on taxpayer compliance. These results suggest that tax collection effectiveness does not strengthen the relationship between taxpayer awareness and compliance. The study recommends that the government improve tax service quality through staff training, effective use of information technology, and more intensive tax outreach programs. Future researchers are encouraged to explore other factors, such as tax sanctions and incentives, that may influence taxpayer compliance.